The Impact of Operating Cash Flow and Current Ratio on the Profitability in Construction Industry (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2020)
The quality of works and a good reputation on the market are the main factors that lead to the success of a construction business. That is why most of the projects carried out in this sector involve the provision of performance guarantees which are mainly constituted by retaining the amounts from each payment. This impacts the cash, but also the liquidity ratios of the entities. The purpose of our research is to analyze the influence of the operating cash flow and the current liquidity ratio on the profitability in the case of construction companies. For this, we have developed a linear regression model on crosssection financial data related to a single reporting year and obtained from construction companies in western Romania. The results we have obtained did not reveal statistical significance for the exogenous variables used in the model. However, we consider it important to deepen the problem of cash flows and the ability of construction companies to meet their short-term obligations in the context of retaining performance guarantees. Further research in this regard based on panel data for several financial periods could provide relevant results.